Learning Concentration Level of Students at Faculty of Nursing Universitas Padjadjaran (An Overview of The Z Generation) - Asti Hanifah; Efri Widianti; Kurniawan Yudianto (Universitas Padjadjaran, 2018)
Generation Z is a generation that has grown in the digital era and is dependent on the internet. One of the features of the internet that is most accessed by this generation is social media. Social media as the information source has a negative impact, especially related to academic processes in the university, namely the learning concentration disorder. Students as part of the Z gene is a population that uses various gadgets (gadgets), so that they are at risk of experiencing learning concentration disorders. The purpose of this study was to describe the level of concentration of learning in students of the Nursing Faculty of Padjadjaran University. This research is quantitative descriptive. The sample was taken using the proportionate stratified random sampling technique from the population of the Nursing Faculty of Padjadjaran University (n = 240). Data were collected using concentration learning questionnaires and analyzed descriptively. The results showed that 40 students (16.7%) had low levels of learning concentration, 166 students (69.2%) with moderate learning concentration levels and 23 (14.2%) with high levels of learning concentration. The conclusion of this study is that most of the Nursing Faculty students of Padjadjaran University have a moderate level of learning concentration. It is recommended to apply varied methods and learning styles in learning activities so that the level of concentration of student learning can be increased.